STRUKTUR DAN KOMPOSISI SERANGGA AIR DI RAWA LEBAK JUNGKAL KABUPATEN OGAN KOMERING ILIR PROVINSI SUMATERA SELATAN - Rizal, Syamsul (Faculty of Mathematics and Natural Science, Universitas PGRI Palembang, 2013)
This study aims to determine the structure and composition of insects in the swamp water of Jungkal Ogan Ilir on South Sumatera province, in June to September 2012. Identification of aquatic insects in the Laboratory of Biology, Faculty of Mathematics and Natural Sciences University of PGRI Palembang. The results showed the relative density , relative frequency , relative dominance at station 1 ( Kumpai copper ) is Pelocoris femoratus and station 2 ( Lotus ) is Parapoyonx sp. Insects are the most dominant with the highest importance value index station 1 is Pelocoris femoratus, station 2 Parapoyonx sp . While the insect species diversity index of water at station 1 of 2.02, at station 2 of 1.25 and index between stations by 46 %. Key words : Insects water , lebak swamp deling, structure , composition